Assessing Connections in an Agricultural Community Using Social Network Analysis. Issue 2 (3rd April 2021) - Beseler, Cheryl L.; Keeney, Annie J.; Garratt, Robyn; Wertheimer, Alix; Stallones, Lorann
ABSTRACT: Agricultural workers experience higher rates of injury and illness than other occupational groups. NIOSH-supported agricultural centers in the U.S. are funded to reduce injury and illness but require effective partnerships with other agricultural organizations to achieve this goal. Our purpose was to understand the structure of agricultural organization connections within six states in the western U.S., including how different types of organizations connect to one another, and specifically where the High Plains Intermountain Center for Agricultural Health and Safety (HICAHS) is positioned in the agricultural organization network. An electronic survey was distributed to contacts within organizations that had a previous history with HICAHS leadership and advisory board members. The survey asked respondents about their position in the organization, years with the organization and frequency of contact in the past year. A social network analysis was undertaken to assess the connections between agricultural organizations using measures of centrality (density, closeness, betweenness), cliques, clusters, and brokers. A two-tier structure was identified with a core group of 21 organizations and a peripheral group of 30 organizations. Influence was centered in the core group as evidenced by high centrality scores with minimal bridging between organizations. HICAHS was on the periphery, but on the cusp of being in the core. Agricultural producers, agricultural extension and insurance companies were central in the network. Centers are in a unique position to promote collaboration with stakeholders. The social network analysis identified missing connections that need further development in order to address agricultural safety and health.